Analisis Perbandingan Performa Web Service Menggunakan Bahasa Pemrograman Python, PHP, dan Perl pada Client Berbasis Android - Achmad Fauzi Harismawan; Agi Putra Kharisma; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In the application development of mobile devices must pay attention to the efficiency in terms of resource usage, in addition mobile device applications are very sensitive to delay. One of the factors that can cause delay is the process done on the web service. The speed of the process in the web service depends on the programming language used, the programming language can also affect the use of CPU (Central Processing Unit) and memory on the server. Therefore, it is necessary to analyze the performance of web service to know the difference of CPU usage (Central Processing Unit), memory, and speed of execution of programming language used in web service. In this research, programming languages used are Python, PHP and Perl using CGI (Common Gateway Interface) on Apache web server accessed via mobile device with Android platform. After the experiment, it was found that Perl programming language has the fastest execution speed while the Python programming language has CPU usage (Central Processing Unit) and the least memory..